ANTIMICROBIAL ACTIVITY OF PIPERACILLIN AGAINST CLINICAL ISOLATES: STUDIES ON SENSITIVITY CHANGES OVER THE YEARS - DEGUCHI, KOICHI (CHEMOTHERAPY, 1988)
Five clinical areas were defined as research subjects for the Piperacillin Research Group (Chairman, YASUSHI UEDA, The Jikei University School of Medicine) which was founded in June 1985. For bacteriological investigation, clinical isolates were collected from the following subject areas:(1) infections associated with tumors, (2) combination therapy of piperacillin with aminoglycosides in intractable respiratory tract infections, (3) combination therapy in abdominal surgery, (4) prophylactic chemotherapy in urology and (5) burns in emergency medicine. The minimal inhibitory concentrations (MIC) of PIPC against the isolates thus collected, including strains obtained directly from patients, were determined and compared with the results of similar studies which were then presented at the New Drug symposium of the 23 rd Eastern Congress of the Japanese Society of Chemotherapy held in November, 1976. 1) No appreciable differences were observed between the new and old data regarding MIC50and MIC80of PIPC againstE. faecalis, E. coli, K. pneumoniae, Enterobacter spp., P. aeruginosa, H. influenzaeandBacteroidesspp., when cultured with an inoculum size of 106cfu/ml. AgainstS. aureus, however, MIC50and MIC80havc changed greatly over the years, from 1.56μg/ml to 50μg/ml and from 6.25μg/ml to>100μg/ml, repectively. 2) Strains ofS. aureushighly resistant to penicillins (PCs) were frequently detected in this study. The results of further investigation showed most of these to be methicillin-resistantS. aureus (MRS A). 3) We confirmed that PIPC is retaining its antimicrobial activity against the major clinical isolates except for MRSA even today in the late 1980's.